RFID Based Universal Transaction System - Attar, Farida; Bhatkar, Amina; Haider, S Hasan; Kadiwala, Tahir Abbas (International Journal of Scientific Research in Computer Science and Engineering, 2020)
Radio Frequency Identification (RFID) makes use of electromagnetic fields to identify objects. This characteristic can be used to identify RFID tags that come in the vicinity of the reader. These tags can be in the form of cards with general details of the user that will allow cashless transactions. As the world is moving towards a digital era, cashless payments are quite in demand. Smart cards that need to be swiped are vulnerable to skimming attacks and data theft. Thus, there is a need to have a cashless transaction system that is fast as well as secure and allows hassle-free transactions. Through this paper, we propose a novel approach to develop a cashless transaction system based on RFID that can be deployed anywhere to enable faster, smoother and secure transactions. The users of the system will have to be pre-registered and all the user related information will be saved in a MySQL database and the system will be programmed using Python. The RFID reader will interact with an Arduino Board and for user input, IR remote will be used.